2007
DOI: 10.1002/ibd.3780050310
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic bone disease in adults with inflammatory bowel disease

Abstract: Bone loss is seen frequently in those with intlammatory bowel disease (IBD). It appears to be more common in those with Crohn's disease than in those with ulcerative colitis. Corticosteroids play an important role in the development of osteoporosis. The prevalence of osteoporosis in IBD, the ef-fects of corticosteroids on bone metabolism, and treatment options are reviewed. Key Words: Inflammatory bowel disease-Crohn's disease-Ulcerative colitis-osteoporo- sis-Osteomalacia-Corticosteroid-induced osteoporosis.~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 113 publications
0
6
0
2
Order By: Relevance
“…[1][2][3][4] It is also debatable which is the most appropriate method to evaluate the presence of MBD in this group of patients. In the present study, DXA was used because it is the method recommended in the last consensus published by ECCO (European Crohn's and Colitis Organization).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] It is also debatable which is the most appropriate method to evaluate the presence of MBD in this group of patients. In the present study, DXA was used because it is the method recommended in the last consensus published by ECCO (European Crohn's and Colitis Organization).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity was assessed using Jackson's questionnaire, 18 which categorized subjects in three different levels: low (0), intermediate (1), and high (2). To improve statistical power and because physical activity was not evaluated in some patients and controls, we considered physical activity on two levels: sedentary versus intermediate/active.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-sectional studies have reported that the prevalence of reduced bone density to be between 3% and 92% in patients with Crohn's disease (CD) and between 0% and 85% in patients with ulcerative colitis (UC) (3,4), with many studies suggesting that patients with CD are more at risk of developing osteopenia than patients with UC (5,6). The main implication of having osteoporosis is that it significantly increases the risk of fractures and population case-control studies have confirmed that patients with IBD have a higher incidence of fractures than the general population (7).…”
mentioning
confidence: 99%
“…Este estudo transversal confirma os relatos prévios de alteração da densidade mineral óssea nos pacientes com DII (2,12,21) . A população estudada tem os valores da DMO significativamente menores (P <0,05) em relação aos indivíduos saudáveis, em todas as regiões ósseas avaliadas (coluna lombar, colo de fêmur e fêmur total).…”
Section: Discussionunclassified
“…Poucos pacientes apresentavam índice de atividade moderado e nenhum deles tinha atividade intensa, conforme os índices aplicados. Talvez outros parâmetros de atividade inflamatória e do metabolismo ósseo, como a dosagem dos mediadores inflamatórios e marcadores bioquímicos de reabsorção óssea, apresentem maior correlação com as anormalidades do metabolismo ósseo (1,2,13) . O efeito deletério do corticóide no metabolismo ósseo é bastante conhecido, porém é controversa a relevância das doses e tempo de uso do corticóide exógeno como fator causal na osteoporose (20,26,27) .…”
Section: Discussionunclassified